Des SfN avant l’heure : ce que nous en disent les opérations de mitigation urbaine en zone inondable. Le cas des villes ligériennes - Marie Fournier; Mathilde Gralepois (Développement Durable et Territoires)
In France, the urban development of floodplains is increasingly attempting to combine flood risk management, recreation, education, biodiversity and environmental preservation. This article proposes a critical reading of several risk mitigation projects through the lens of the Nature-based Solutions (NBS) concept. In the beginning of the 21st century, several projects of flood mitigation in urban context already proposed an embodiment and a formalisation of the main principles of NBS. To put it another way, these projects initiated by the French local authorities of the Loire River basin since the beginning of the 2000s have in fact fully integrated NBS principles, to a greater or lesser extent, without explicitly using the concept. The NBS framework is now a normative reference framework based on three aspects that allows mitigation projects to be re-examined a posteriori: synergies between different functions; adaptation to local situations over time ; and the participation of local stakeholders. The challenge is to understand how the concept of NBS, although not yet widely used by planners, is already partly present in past projects.